Flame behaviour of magnesium and aluminium hydroxide-filled polymer composites used in power and telecom cables. (21st April 2022) - Roda, Elena; Galletti, Franco; Truscello, Ada; Gambarotti, Cristian
ABSTRACT: The effect of flame contact on Low Smoke Zero Halogen (LS0H) polyethylene-based model composite used for power cable has been investigated, focusing the attention on the fate of aluminium trihydroxide (ATH) and magnesium dihydroxide (MDH) utilized as flame retardant fillers. By using a flame reproducing the calorific value of EU CPR Regulation, during the contact with flame, the composite with magnesium hydroxide shows the formation of intermediate carbonate, which further decomposes giving the oxide. The same finding was observed in the blank test performed on pure MDH. This feature was not observed in ATH composite and pure one. The higher decomposition temperature of MDH, together with the formation of carbonate could play a key role in the higher efficiency of MDH compared to that of ATH. Moreover, we report that the stearic acid, present in the composite as compatibiliser and as processing aid, seems to migrate towards the external surfaces.